Uncomplicated Plasmodium vivax malaria in pregnancy associated with mortality from acute respiratory distress syndrome - McGready, Rose (BioMed Central, 2014)
The association between severe malaria and Plasmodium vivax species is contentious. On the Thai-Myanmar border, all pregnant women are followed systematically with active weekly malaria screening. Over a 27-year period of providing antenatal care, 48,983 have been prospectively followed until pregnancy outcome (miscarriage or delivery) and 4,298 women have had P. vivax detected at least once. Reported here is the first known P. vivax-associated death amongst these women. The initial patient presentation was of uncomplicated P. vivax (0.5% parasitaemia) in a term, multigravida woman who responded rapidly to oral artesunate and mefloquine treatment, clearing her blood stage parasites within 48 hours. The patient appeared well, was ambulatory and due to be discharged but became unwell with acute respiratory distress syndrome (ARDS) requiring ventilation three days (67 hours) into treatment. Despite induction and delivery of a stillborn foetus, ventilatory requirements increased and the patient died on day 7. The patient had a low body mass index. Sensitive detection with nested PCR confirmed only the presence of P. vivax species and concomitant infections such as tuberculosis and human immunodeficiency virus (HIV) were also ruled out. The contemporaneous treatment of acute uncomplicated P. vivax and the onset of ARDS on day 3 in this patient implies a possible but unconfirmed association with death in this patient. Assuming this death was caused by P. vivax, the risk of ARDS-related maternal mortality in this setting did not differ significantly between Plasmodium falciparum and P. vivax (0.24 per 1,000 (1/4,158) versus 0.23 per 1,000 (1/4,298), contrary to the increased risk of maternal mortality from P. falciparum compared to P. vivax, 2.89 per 1,000 (12/4,158) versus 0.23 per 1,000 (1/4,298), P = 0.003.